Collective actions for the control of type 2 diabetes mellitus in Primary Healthcare: An experience report (Research, Society and Development, 2021)
This study aimed to report the experience of providing collective care for people with type 2 diabetes mellitus in a Family Healthcare Unit in the western sanitary district of Ribeirão Preto, São Paulo. It is an experience report built from the scope of qualitative research of characteristic research-action. Data collection took place between August and October 2018 and aimed to identify and characterize people with diabetes regarding the need for inclusion in the intervention group for collective care. It was found 126 people with type 2 diabetes mellitus, of which 70.6% were female, mean age 59.7 years, 72.2% had a concomitant diagnosis of systemic arterial hypertension, 31.7 % had a delay in the frequency of medical appointments or laboratory tests and 17.9% had glycated hemoglobin above 8% in the last test performed. Forty people were invited and 60% of them attended to participate in collective actions aimed at controlling diabetes. During the meetings, topics of diabetes education, updates on medication prescriptions and requests for laboratory tests were addressed. It is believed that the strategy used in this intervention can be reproduced in other Primary Health Care services to ensure comprehensive care for people with diabetes.